2005
DOI: 10.1590/s0103-97332005000700045
|View full text |Cite
|
Sign up to set email alerts
|

Statefinder revisited

Abstract: The quality of supernova data will dramatically increase in the next few years by new experiments that will add high-redshift supernova to the currently known ones. In order to use this new data to discriminate between different dark energy models, the statefinder diagnostic was suggested [1] and investigated by Alam et al.[3] in the light of the proposed SuperNova Acceleration Probe (SNAP) satellite. By making use of the same procedure presented by these authors, we compare their analyzes with ours, which sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…So here we quote the observed uncertainties on diagnostic parameters obtained in previous works. Uncertainties on S (1) 3 and S (1) 4 from current observations or estimated from simulations can be found in [34,[69][70][71][72][73][74]. It was found that they are rather difficult to measure-for most of the fit results, the uncertainties on S…”
Section: Probing Deviations From λCdm In the Iλcdm Modelsmentioning
confidence: 99%
“…So here we quote the observed uncertainties on diagnostic parameters obtained in previous works. Uncertainties on S (1) 3 and S (1) 4 from current observations or estimated from simulations can be found in [34,[69][70][71][72][73][74]. It was found that they are rather difficult to measure-for most of the fit results, the uncertainties on S…”
Section: Probing Deviations From λCdm In the Iλcdm Modelsmentioning
confidence: 99%
“…Since these publications, several efforts have been made to explain these observations (Cunha et al 2009;Frieman et al 2008;Linder 2008;Linder & Huterer 2005;Samsing & Linder 2010;Freaza et al 2002;Ishida 2005;Ishida et al 2008, and references therein). In a standard analysis, dark-energy models are characterized by a small set of parameters.…”
Section: Introductionmentioning
confidence: 99%
“…So here we quote the observed uncertainties on diagnostic parameters obtained in previous works. Uncertainties on S 4 from current observations or estimated from simulations can be found in [34,[69][70][71][72][73][74]. It was found that they are rather difficult to measure-for most of the fit results, the uncertainties on S 4 are larger than the maximum differences [5% (4%) and 15% (3%)] between the ΛCDM model and the IΛCDM1 (IΛCDM2) model, indicating that neither the IΛCDM1 model nor the IΛCDM2 model can be well distinguished from the ΛCDM model.…”
Section: Probing Deviations From λCdm In the Iλcdm Modelsmentioning
confidence: 99%